Genome‐wide transcriptomic changes reveal the genetic pathways involved in insect migration. Issue 16 (12th July 2022) - Doyle, Toby; Jimenez‐Guri, Eva; Hawkes, Will L. S.; Massy, Richard; Mantica, Federica; Permanyer, Jon; Cozzuto, Luca; Hermoso Pulido, Toni; Baril, Tobias; Hayward, Alex; Irimia, Manuel; Chapman, Jason W.; et al.
Abstract: Insects are capable of extraordinary feats of long‐distance movement that have profound impacts on the function of terrestrial ecosystems. The ability to undertake these movements arose multiple times through the evolution of a suite of traits that make up the migratory syndrome, however the underlying genetic pathways involved remain poorly understood. Migratory hoverflies (Diptera: Syrphidae) are an emerging model group for studies of migration. They undertake seasonal movements in huge numbers across large parts of the globe and are important pollinators, biological control agents and decomposers. Here, we assembled a high‐quality draft genome of the marmalade hoverfly ( Episyrphus balteatus ). We leveraged this genomic resource to undertake a genome‐wide transcriptomic comparison of actively migrating Episyrphus, captured from a high mountain pass as they flew south to overwinter, with the transcriptomes of summer forms which were non‐migratory. We identified 1543 genes with very strong evidence for differential expression. Interrogation of this gene set reveals a remarkable range of roles in metabolism, muscle structure and function, hormonal regulation, immunity, stress resistance, flight and feeding behaviour, longevity, reproductive diapause and sensory perception. These features of the migrant phenotype have arisen by the integration and modification of pathways such as insulin signalling for diapause and longevity, JAK/SAT for immunity, and those leading to octopamine production and fuelling to boost flight capabilities. Our results provide a powerful genomic resource for future research, and paint a comprehensive picture of global expression changes in an actively migrating insect, identifying key genomic components involved in this important life‐history strategy.